Community junior sport sponsorship: an online experiment assessing children’s responses to unhealthy food v. pro-health sponsorship options - Dixon, H.; Scully, M.; Wakefield, M.; Kelly, B.; Pettigrew, Simone (Cambridge University Press, 2017)
Copyright © The Authors 2017 Objective: To explore children’s responses to sponsorship of community junior sport by unhealthy food brands and investigate the utility of alternative, pro-health sponsorship options. Design: Between-subjects experiment, with four sponsorship conditions: A, non-food branding (control); B, unhealthy food branding; C, healthier food branding; D, obesity prevention campaign branding. Setting: Online experiment conducted in schools. Participants were shown a junior sports pack for their favourite sport that contained merchandise with branding representing their assigned sponsorship condition. Participants viewed and rated the sports pack, completed a distractor task, then completed questions assessing brand awareness, brand attitudes and preference for food sponsors’ products. Subjects: Students in grades 1 to 3 (aged 5–10 years; n 1124) from schools in metropolitan Melbourne, Australia. Results: Compared with the control condition, there were no significant effects of unhealthy food branding on awareness of, attitudes towards or preference for these brands. Exposure to healthier food branding prompted a significant increase in the proportion of children aware of these brands, but did not impact attitudes towards or preference for these brands. Exposure to either healthier food branding or obesity prevention campaign branding prompted a significant reduction in the proportion of children showing a preference for unhealthy food sponsor products. Conclusions: The sponsorship of children’s sport by healthier food brands may promote awareness of these brands and healthier sponsorship branding may reduce preferences for some unhealthy food products. Establishing and implementing healthy sponsor criteria in sports clubs could forge healthier sponsorship arrangements and help phase out unhealthy food and beverage sponsors.